Long-term disease stabilization following treatment with erlotinib in heavily pretreated patients with wild-type epidermal growth factor receptor non-small-cell lung carcinoma: Two case reports - Sakellakis, Minas (Mol Clin Oncol, 2016)
Lung adenocarcinomas carrying epidermal growth factor receptor (EGFR) mutations have been identified as a unique group of entities that depend on EGFR for their proliferation and metastasis. The introduction of reversible EGFR tyrosine kinase inhibitors, such as erlotinib, has significantly affected the management of metastatic disease in this subset of patients. Interestingly, although erlotinib is highly effective in patients with EGFR mutations, it may occasionally prove useful, even in the absence of mutations. We herein present the course of two heavily pretreated patients who achieved remarkable disease stabilization over several years, despite harbouring no EGFR mutations. Our cases underscore the fact that further research is required to identify which subset of patients will benefit the most from this treatment, as a substantial minority may present with favourable outcomes.